Corporate Governance on Dividend Policy and Firm Value in LQ45 Index Companies - Wati, Erna; Julianto, Julianto; Dewi, Sari (E-Jurnal Akuntansi; Vol 34 No 7 (2024), 2024)
This study aims to analyze the effect of corporate governance, which includes family, institutional, managerial, and foreign ownership, on dividend policy and firm value, as well as the moderating role of independent directors in LQ45 companies. Purposive sampling method is used to select 43 LQ45 companies as research samples. The analysis method used is multiple linear regression analysis using data from the annual reports of companies listed on the Indonesia Stock Exchange (IDX). The findings of this study state that institutional ownership has a significant negative effect on dividend policy, with the independent director variable as a moderating variable. In addition, this study also shows that there is no effect of corporate governance through dividend policy as a mediating variable on firm value. Keywords: Corporate Governance; Dividend Policy; Firm Value; Ownership Structure.